PENGARUH MANAJERIAL KEPALA SEKOLAH, BUDAYA ORGANISASI DAN MUTU TERHADA KINERJA SEKOLAH DASAR DI KABUPATEN ACEH BARAT - Wansa Amin; Marwan Marwan; Alfi Syahrin (Puteri Hijau : Jurnal Pendidikan Sejarah, 2024)
The research objectives are 1) To determine the managerial influence of elementary school principals in West Aceh Regency on the quality of elementary school education in cluster 1 of Meureubo District in West Aceh Regency; 2); To determine the influence of school organizational culture on the quality of elementary school education in cluster 1 of Meureubo District in West Aceh Regency and 3). To determine the influence of school principal performance on the quality of elementary school education in cluster 1 of Meureubo District in West Aceh Regency. This research uses descriptive quantitative methods. According to Marwan, et al (2023) quantitative research involves and collects numerical data with control variables. Data collection techniques use questionnaires or questionnaires which are distributed to research samples. Meanwhile, data processing and analysis techniques use parametric statistical methods and tools. Population 449 people, sample 82 people, determining the number of samples in this study using the Taro Yamane formula. using an error acceptance of 10%. Based on the results of data processing and analysis, it can be concluded that there is an influence of managerial principals, organizational culture and principal performance on the quality of elementary school education in West Aceh Regency. Almost half of them answered that there is an influence of managerial principals, organizational culture and principal performance on the quality of elementary school education in cluster 1 Meureubo District in West Aceh Regency. This can be seen in the results of the average percentage of respondents who agreed, which was 41% and the percentage who answered very influential was 34%. Furthermore, a small number of respondents said it had no influence with a percentage of 10% of answers, 10% said it had very no influence and 5% answered doubtfully that there was an influence of the principal's managerial, organizational culture and principal performance on the quality of elementary school education in cluster 1 of Meureubo District. in West Aceh Regency.